Stress-strain Constitutive Models Along the Grain of Original Bamboo Based on Classification - Zhili Cui; Zhenhua Jiao; Wei Tong; Pan Li (BioResources, 2024)
To establish the constitutive model of original bamboo, the tensile and compressive tests along the grain of original bamboo were investigated. The original bamboo was graded according to the elastic modulus, and a stress-strain constitutive model of original bamboo was proposed. The results of the study show that the tensile failure mode of original bamboo along the grain is brittle failure, and the compression along the grain is ductile failure. The bamboo was divided into three grades I, II, and III, and the proportion of II and II was more than 80%. A linear constitutive model was used for tension along the grain of original bamboo, a "three-fold" model was used for simplified constitutive model for compression along the grain, and the Sargin model was used for accurate constitutive model. The classification method proposed in this paper can result in the efficient utilization of bamboo resources, and the proposed constitutive model can promote the analysis and engineering application of original bamboo architecture.